Evaluation of the Result of Surgical Repair of Open Achilles Tendon Injuries by Pulling Down of The Proximal Tendon - Ahmed, Samil Uddin; Hasan, Md Habibul; Haque, Md Ariful; Haque, Md Enamul; Imam, Zafar (TAJ: Journal of Teachers Association, 2022)
Introduction: In this series, we used five parameters according to the Juhana Leppilahti Modified scoring system to assess final outcome of surgical repair of open achilles tendon repair : the ability to stand on affected tiptoe unsupported, range of motion of affected side of the ankle, power of plantar flexion, calf muscle wasting. Methods: The study was designed as a prospective experimental study conducted at Rajshahi Medical College Hospital and one private hospital of Rajshahi from January 2006 to December 2019. The study was carried out on 50 patients irrespective of age and sex. Pulling down the proximal tendon was the operative procedure. Follow-up was undertaken at the private chamber, the outpatient department and in the orthopedic ward. Result: Among 50 patients, 38(76%) were male, and 12(24%) were female. The mean delay of repair was 6 hours 7 minutes, with a standard deviation ± 2.362 minutes. The mean age was 30.02 years with SD± 7.7. In our study, median level of cut was 3.0 cm proximal to the insertion of tendon Achilles and where the interquartile range was 2.5 to 3.5 cm. The mean follow-up period was six months with a standard deviation of 2.37. Common complications were superficial skin infection in four cases (37%), mild swelling in four cases (36%), ugly scar in two cases (18%), and wound gap in one case (9%). In our study, no major complications occurred, but minor complications like superficial skin infection and delayed wound healing were effectively dealt with an oral antibiotic with no long-term sequelae. At 16 weeks of follow-up, among 50 patients, 90% (45) can stand on affected tip toes unsupported, around 4 cases (8%) cannot stand on tiptoes of affected foot can't support but able to stand on affected foot with unsupported. Around 2% (1 case) failed to stand on the affected foot without support due to severe infection and wound gap. The eventual outcomes were excellent in 28 cases (56%), good in 16 cases (32%), fair in 4 cases (8%), and poor in 2 cases (4%). In this study, satisfactory Result was obtained after immediate repair of acute open tendon Achilles tendon injury cases. According to Juhana Leppilahti Modified Score at 95% confidence interval, satisfactory outcome was 78.99% to 97.00%. Conclusion: Early repair of open tendo Achilles injuries, complete or partial, provided an effective outcome, which was comparable with the Result described in others. TAJ 2021; 34: No-2: 15-23